Fractal textures of bovine serum albumin films - Glibitskiy, G. G. (Biophysical Bulletin, 1970)
The texture features of the films obtained from solutions of bovine serum albumin (BSA) in the presenceof sodium and copper ions are considered. The apparatus for producing films and the absorption spectraof BSA in the UV wavelength range are presented. The films have been received from BSA solutionswith concentration of 0.41 mg/ml in the presence of salt NaCl at a concentration of 20 mM and in thepresence of salt CuCl2 with concentrations of 0.1 mM and 0.4 mM. Texture films of BSA, human serumalbumin and calf thymus DNA are compared. The obtained scale invariant fractal textures are similar totextures which are formed on the films surface from the DNA solutions. Presence in solution of heavymetal ions forming compounds with albumin molecules prevents the formation of scale invariant fractaltextures on films from these solutions.